2018
DOI: 10.1016/j.beem.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Novel mechanisms of G-protein-coupled receptors functions: AT1 angiotensin receptor acts as a signaling hub and focal point of receptor cross-talk

Abstract: AT angiotensin receptor (ATR), a prototypical G protein-coupled receptor (GPCR), is the main receptor, which mediates the effects of the renin-angiotensin system (RAS). ATR plays a crucial role in the regulation of blood pressure and salt-water homeostasis, and in the development of pathological conditions, such as hypertension, heart failure, cardiovascular remodeling, renal fibrosis, inflammation, and metabolic disorders. Stimulation of ATR leads to pleiotropic signal transduction pathways generating arrays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 98 publications
1
30
0
1
Order By: Relevance
“…Thus, our data reveal for the first time the possible interplay between AT1R and PAR1 when coexpressed in HEK293 cells. This comes to extend the list of GPCR members potentially interacting or interplaying with AT1R (Takezako et al, 2017;Toth et al, 2018) or PAR1 (Arachiche et al, 2013;Lin and Trejo, 2013) reported in many contexts and models.…”
mentioning
confidence: 96%
“…Thus, our data reveal for the first time the possible interplay between AT1R and PAR1 when coexpressed in HEK293 cells. This comes to extend the list of GPCR members potentially interacting or interplaying with AT1R (Takezako et al, 2017;Toth et al, 2018) or PAR1 (Arachiche et al, 2013;Lin and Trejo, 2013) reported in many contexts and models.…”
mentioning
confidence: 96%
“…In addition to dual drug therapy, the ability of the CB1R to dimerize with other receptors can also be leveraged to design novel therapies. The CB1R has a high tendency to crosstalk with several different GPCRs, including but not limited to the AT1R and the opioid receptors [ 141 , 145 , 602 , 603 , 604 ]. Since receptor heteromers are selectively expressed in only distinct pathological conditions [ 605 , 606 ], targeting heteromeric complexes has been discussed as a viable therapeutic strategy [ 607 ].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Gq protein signaling can also regulate Rho-GEFs leading to the activation of the Rac or Rho/ROCK signaling pathways. AT1R coupled to Gi/o inhibits adenylyl cyclase and some Ca++ channels and activates Rho kinase (Toth, Turu, Hunyady, & Balla, 2018). The Gβ2 subunit of the G protein interacted with specific nucleosome core histones and sequence motif of several transcription factors (Bhatnagar et al, 2013).…”
Section: Angiotensin Type 1 Receptor and Blood Pressurementioning
confidence: 99%
“…β-Arrestins also serve as docking platforms for ERKs leading to a different mode of MAPK signaling cascade involved mainly in cell proliferation and survival (Kim, Ahn, Rajagopal, & Lefkowitz, 2009). These events are called second wave AT1R signaling (Toth et al, 2018). The G protein-dependent and -independent signaling waves of AT1R occur in different time and space in a cell.…”
Section: Angiotensin Type 1 Receptor and Blood Pressurementioning
confidence: 99%